Inside Cover: Ultrasound‐ and Microwave‐Assisted Preparation of Lead‐Free Palladium Catalysts: Effects on the Kinetics of Diphenylacetylene Semi‐Hydrogenation (ChemCatChem 6/2015). Issue 6 (March 2015) - Wu, Zhilin; Cherkasov, Nikolay; Cravotto, Giancarlo; Borretto, Emily; Ibhadon, Alex O.; Medlock, Jonathan; Bonrath, Werner
<x xml:space="preserve">Abstract</x> The cover picture shows the pivotal role of ultrasound and microwaves in the one‐pot preparation of a lead‐free Pd‐catalyst for selective hydrogenation. In their Full Paper, Z. Wu et al. show that sonication in the presence of a capping agent and reduction by microwave heating gives monodisperse Pd nanoparticles supported on boehmite. The catalyst is approximately seven times as active as a commercial Lindlar catalyst per unit of Pd mass taken, and only 6 % (at 95 % conversion) less selective towards semi‐hydrogenation. This investigation was performed by the Universities of Turin (Italy) and Hull (UK) in collaboration with DSM Nutritional products Ltd, Basel (Switzerland) and was funded by the FP7 project MAPSYN. The article highlighted by this cover can be found on p. 952 ff. of Issue 6, 2015.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>